Investigation of the negative ionospheric response of the 8 September 2017 geomagnetic storm over the European sector. Issue 4 (15th August 2022) - Oikonomou, Christina; Haralambous, Haris; Paul, Ashik; Ray, Sarbany; Alfonsi, Lucilla; Cesaroni, Claudio; Sur, Dibyendu
Highlights: Negative ionospheric response due to mid-latitude trough displacement over Europe. LSTIDs were detected during the 8 September storms accompanied with Spread F. TEC, foF2, hmF2, Spread-F were more prominent over northern mid-latitude regions. Abstract: In this study, we investigate the negative ionospheric response over the European sector during two storms that took place on 8 September 2017, primarily, by exploiting observations over ten European locations. The spatial and temporal variations of TEC, foF2 and hmF2 ionospheric characteristics are examined with the aim to explain the physical mechanisms underlying the strong negative ionospheric response. We detected very sharp electron density (in terms of foF2 and TEC) decrease during the main phases of the two storms and we attributed this phenomenon to the large displacement of the Midlatitude Ionospheric Trough (MIT). Our study also revealed that the two storms show different features caused by different processes. In addition, Large Scale Traveling Ionospheric Disturbances (LSTIDs) were observed during both storms, followed by enhanced Spread F conditions over Digisonde stations. The regional dependence of ionospheric storm effects was demonstrated, as the behavior of ionospheric effects over the northern part of Europe differed from that over the southern part.